(untitled) (Research Nepal Journal of Development Studies, 2023)
The Kālacakra tantra and its tradition is a philosophical esoteric Buddhist practice which has its roots in Nepal. This practice has developed and thrived over the centuries. This study dives into the origin and development of the profound Buddhist Tāntrik text, with a particular focus on the contributions of Nepal and in during its formative period. Drawing from various sources, it tries to trace its historical context and transmission of the Kālacakra Tantra. It highlights the significant role played by Nepalese scholars in translating, disseminating and transmitting this esoteric values. The primary sources of this study are Saṃskṛit text such as Vimalaprabhātika and Sekoddeśaṭīkā by are used. The translation a Tibetan text deb ther sngon po by Gö Lotsawa, Blue Annals is also used as the primary source for this study